Abandoned oil and gas well site environmental risk estimation. Issue 7 (14th September 2017) - Thiessen, Ron J.; Achari, Gopal
ABSTRACT: The article estimates the environmental risk (i.e. potential adverse biological receptor effects) of abandoned yet unreclaimed well sites in Alberta. This estimation was completed through a statistical analysis of publicly available environmental data on 298 well sites. The connections among contaminant hazards, exposure pathway-routes and biological receptors were analyzed using fuzzy logic. Based on the available data, well type is the only predictor required to classify the environmental risk of a site into one of four adverse effect (AE) classes. Generally, the large majority of well sites in the data-set did not pose a significant AE. At well sites posing a significant AE, produced water impacts were the primary contributor.